Karateristik Massa Air di Perairan Ekuator Pasifik Barat pada Bulan Agustus 2018 - Duaitd Kolibongso (Jurnal Sumberdaya Akuatik Indopasifik, 2020)
The Western Pacific Equator waters are a meeting place for water masses coming from the Northern and Southern Hemispheres. This study aims to identify the characteristics of water masses formed in the waters of Northern Papua. The study of water mass characteristics in the northern waters of Papua was carried out based on reanalysis data from the World Ocean Atlas (WOA) in August 2018. There were 12 stations divided into 3 transects to be analyzed in this study, namely transect 1 and transect 2 which stretched north-south and transect 3 which stretches east-west. The analysis were performed by method of the core layer and was processed with Sofware Ocean Data View (ODV). The results showed in the waters of North Papua there was a meeting of 2 water masses from the North Pacific and South Pacific. The water masses characteristics in latitudes <5 oLU are affected by surface and intermediates of the South Pacific carried by the Papua New Guinea Coastal Current that flows along the northern coast of Papua New Guinea and into Papua waters and beyond into the waters of the Halmahera Sea. Whereas the mass of water in latitudes > 5 oLU is dominated by surface and intermediate water masses from the North Pacific carried by North Equatorial Counter Current.